Who's learning from whom? Grassroots International NGOs learning from communities in development projects. Issue 5 (4th July 2022) - Contreras, Santina; Roudbari, Shawhin
ABSTRACT: Discussions surrounding participation in development projects often frame knowledge exchanges in a unilateral manner. However, in the implementation of participatory activities by grassroots international nongovernmental organizations (GINGOs), community members frequently serve not only as beneficiaries but have essential impacts on the organisations guiding these participatory engagements. In this study, we examine these reciprocal engagement dynamics through a case study analysis of GINGOs based in the US working on development projects with communities in the Global South. Our analysis details ways these organisations are learning and applying knowledge from communities, and the importance of addressing questions of beneficiaries and power dynamics.